Structures of multisubunit membrane complexes with the CRYO ARM 200. (21st July 2022) - Gerle, Christoph; Kishikawa, Jun-ichi; Yamaguchi, Tomoko; Nakanishi, Atsuko; Çoruh, Orkun; Makino, Fumiaki; Miyata, Tomoko; Kawamoto, Akihiro; Yokoyama, Ken; Namba, Keiichi; Kurisu, Genji; Kato, Takayuki
Abstract: Progress in structural membrane biology has been significantly accelerated by the ongoing 'Resolution Revolution' in cryo-electron microscopy (cryo-EM). In particular, structure determination by single-particle analysis has evolved into the most powerful method for atomic model building of multisubunit membrane protein complexes. This has created an ever-increasing demand in cryo-EM machine time, which to satisfy is in need of new and affordable cryo-electron microscopes. Here, we review our experience in using the JEOL CRYO ARM 200 prototype for the structure determination by single-particle analysis of three different multisubunit membrane complexes: the Thermus thermophilus V-type ATPase VO complex, the Thermosynechococcus elongatus photosystem I monomer and the flagellar motor lipopolysaccharide peptidoglycan ring (LP ring) from Salmonella enterica .